BUILDING STUDENT CHARACTER THROUGH PENCAK SILAT PAGAR NUSA: AN ANALYSIS OF EXTRACURRICULAR IMPLEMENTATION AT MADRASAH TSANAWIYAH NEGERI 5 JAMBI CITY - Suwanto, Suwanto; Yahuda, M (Edukasi Islami : Jurnal Pendidikan Islam, 2026)
Background: In the midst of the modernization trend that triggers a moral crisis among adolescents, educational institutions are required to strengthen the cultivation of character values. Madrasah Tsanawiyah Negeri 5 Jambi City answers this challenge by integrating physical, mental, and spiritual aspects through non-academic activities. Research Novelty: This study explores the unique integration of Pencak Silat Pagar Nusa as a character development instrument that bridges traditional martial arts with Islamic moral education in a modern school environment. Objective: To describe the implementation of Pagar Nusa extracurricular activities and evaluate its impact on strengthening students' character. Methods: Using a descriptive qualitative approach with data collection techniques through systematic observation, in-depth interviews, and documentation analysis. The validity of the data is ensured through triangulation of sources and techniques. Results: The Pagar Nusa program was implemented through a synergy of rigorous physical training, Islamic principles, and high discipline standards, which included physical agility and mental exercise materials. The findings show a significant positive transformation in students' character, especially in improving discipline, responsibility (accountability), and strengthening ethics and interpersonal respect. Conclusion: The Pagar Nusa extracurricular has proven to be an effective and integrative character education instrument, succeeding in producing a generation that is physically resilient as well as noble in ethics